PENGGUNAAN ARANG KOMPOS PADA MEDIA TUMBUH ANAKAN MAHONI - Sri Komarayati (Jurnal Penelitian Hasil Hutan, 2004)
This report described  results of  an  application of  two  kinds of  compost charcoals on the growing media of mahoni seedlings(Swietenia rnacropbylla King)for  5-month duration. Objective of this study is to learn such applicationon  the characteristics of seedlings growth.The two kinds of compost charcoals were : the one derived from  tusam litters (Al)  ;  and the other from a mixture of litters and mahoni seeds  (A.2). Results  revealed that  the application of compost charcoal (A1  and A2)  each at 30% dosage could increase height of mahoni seedlings as much as 17.67 -  25.02 cm, which  Is  approximately  3 times greater than  the control.  The compost application also increased girth of mahoni seedling up to twice that of the controls.The application of compost charcoal at  40% dosage of either (Al)  or (A2), however, showed a  smaller increase in height and girth increament compared with the 30% dosage. Cummulatively,the application of compost charcoal could increase the seedling biomass by more than 400%.